PERKEMBANGAN AKUNTANSI DI INDONESIA - Anisa Putri (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2010)
Accounting is a tool to inform the financial information to everyone who needs. Informing such information, it is used the report of accounting or financial report. The dynamics of develophing the standart of accountancy since IAI established in 1957 till now. At last, there are three historical milestones that have been reached in develophing the standard of financial accountancy in Indonesia. First, before activating the money market in Indonesia in 1973. Second, in 1984, and third in 1994 IAI totally revised PAI 1984 it is converted in SAK per 1st October 1994. Since 1994 IAI also pas decided to harmonize with international accountancy standart in develophing it’s standart by declaration, it is hoped that the entity has enough time to prepare as well as possible in anticipating the process on confergence done by IAI.